THE DISTRIBUTION MODEL OF HUMANITARIAN LOGISTICS IN OPTIMIZING DISASTER MANAGEMENT IN PASIGALA IN CENTRAL SULAWESI - Rohmawati, Suci; Moh. Saleh , Husein H.; Syamsuddin, Syamsuddin (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2021)
This research aims to find out the distribution model of humanitarian logistics applied when dealing with natural disasters in Pasigala (Palu, Sigi, and Donggala) and to find out the optimal humanitarian logistics distribution model in dealing with natural disasters in Pasigala, Central Sulawesi. The paradigm in this research is based on the phenomenological paradigm and is qualitative. The research was conducted in the affected area of ​​Pasigala through data collection techniques in the form of interviews with informants consisting of disaster survivors and disaster management institutions from both government and non-government. The analysis tool in this research uses the NVIVO 12 Plus software. The results of the research show that the humanitarian logistics distribution model that has been carried out by the relevant institutions has a different structure. The distribution of logistics is still considered not optimal because there are obstacles that have an impact on new problems such as overlapping logistical assistance in several areas therefore it is necessary to propose a redesign of the humanitarian logistics distribution model based on the results of the analysis that has been carried out. Keywords: Distribution, Logistics, Humanity, Pasigala, Disaster